Non-colorectal intestinal tract carcinomas in inflammatory bowel disease: results of the 3rd ECCO Pathogenesis Scientific Workshop (II) - Egan, L (2014)
Patients with inflammatory bowel diseases (IBD) have an excess risk of certain gastrointestinal cancers. Much work has focused on colon cancer in IBD patients, but comparatively less is known about other more rare cancers. The European Crohn's and Colitis Organization established a pathogenesis workshop to review what is known about these cancers and formulate proposals for future studies to address the most important knowledge gaps. This article reviews the current state of knowledge about small bowel adenocarcinoma, ileo-anal pouch and rectal cuff cancer, and anal/perianal fistula cancers in IBD patients.